Use of the online poisons information database TOXBASE and admissions rates for poisoned patients from emergency departments in England and Wales during 2008 to 2015 - Pyper, Kate, PhD; Robertson, Chris, PhD; Eddleston, Michael, ScD; Sandilands, Euan, MD; Bateman, D. Nicholas, MD (Journal of the American College of Emergency Physicians Open, 2020)
AbstractBackgroundThe impact of poison information services on patient care in hospital, particularly decisions on whether to admit patients after initial attendance at an emergency department (ED), is unclear. In the United Kingdom, the vast majority of poisons information is provided by use of the online poisons information database, TOXBASE. We investigated the relationship between rates of hospital access to TOXBASE and rates of poisoning admissions from EDs in England and Wales to begin to address the interactions between use of poisons information and patient management as reflected by hospital activity. MethodsData were obtained on attendances and admissions due to poisoning for individual National Health Service (NHS) Trusts in both England and Wales, together with data on the overall number of accesses to TOXBASE for drugs (pharmaceuticals and drugs of abuse), from 2008 to 2015. Rates of TOXBASE access and admissions per poisoning attendance in London were clearly different to the rest of England and Wales; London was therefore analyzed separately. Negative binomial generalized additive models were fit, incorporating an interaction effect, for accesses, attendances and admissions to check for variability according to hospital size. Additional models were then fit to assess whether there was any variation in association of overall TOXBASE use with rates of admission for 6 key drug subgroups: antidepressants, paracetamol, antipsychotics, opioids (including all medicines, but excluding heroin), heroin and non‐opioid drugs of abuse. ResultsRates of TOXBASE use per Trust increased across the study period by 39.3% (95% confidence interval [CI] = 34.1%, 44.8%) in England and 76.9% (24.7%, 151.0%) in Wales, showing an increase in TOXBASE use which was substantially greater than the increase in poisoning attendances. Admission rates exhibited seasonality, with lower rates in January and February, increasing by 2.0% (1.0%, 3.1%) in England and 5.8% (5.5%, 5.9%) in Wales toward the middle of the year. The initial model fit indicated that the average proportion of poisoning patients admitted increased with both increasing attendances and increasing TOXBASE use (England and Wales overall, P < 0.0001; England and Wales excluding London, P < 0.0001; London, P < 0.0001). In England and Wales overall, and in London alone, increased TOXBASE access to non‐opioid drugs of abuse advice was associated with a significant decrease in admissions (England and Wales, −0.15% [−0.29%, −0.01%] [ P = 0.032]; London, −1.02% [−1.53%, −0.50%] [ P < 0.0001]). In contrast, increased access to heroin advice was associated with a significant increase in admissions in London (+2.03% [+0.11%, +3.99%] [ P = 0.034]). Increasing access to TOXBASE for paracetamol advice was associated with lower admissions in England and Wales (England and Wales, −0.11% [−0.23%, −0.01%] [ P = 0.036]; England and Wales excluding London, −0.18% [−0.30%, −0.06%] [ P = 0.001]) but higher admissions in London (+0.52% [+0.03%, +1.01%] [ P = 0.035]). ConclusionsWe have shown that greater overall use of TOXBASE by hospitals is associated with a higher proportion of poisoning attendances being admitted. Interestingly, looking at particular drug groups, we found significant associations in both directions between overall TOXBASE use and rates of admission for some drug groups. The current methodology is unable to determine whether such decisions might be appropriate or not. Mixed‐methods research is now required to gain a better understanding of how provision of poisons information affects decisions within the ED.